2015
DOI: 10.4236/jss.2015.38013
|View full text |Cite
|
Sign up to set email alerts
|

A Gravity Model Analysis for Trade between Cameroon and Twenty-Eight European Union Countries

Abstract: The purpose of this empirical analysis is to investigate, based on gravity model, Cameroon's bilateral trade flows with Twenty-Eight European Union countries signatories of the EU-Cameroon Free Trade Agreement (FTA) on the 15 th of January 2009. Though the said Agreement entry into force day was scheduled for the 4 th of August 2014, it is important to analyze the trade trends among these 29 countries. The research findings reveal that Cameroon's bilateral trade with European Union countries is affected positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 9 publications
5
11
0
Order By: Relevance
“…The determinants of Cameroon's foreign trade with 28 trade partners from the European union countries are investigated by the study of Doumble and Belinga (2015). The finding of this study reveals that a bilateral trade between Cameroon and its selected trade partners is positively affected by the economic size of the country and per capita income, and negatively affected by a geographical distance of trading partners.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 85%
“…The determinants of Cameroon's foreign trade with 28 trade partners from the European union countries are investigated by the study of Doumble and Belinga (2015). The finding of this study reveals that a bilateral trade between Cameroon and its selected trade partners is positively affected by the economic size of the country and per capita income, and negatively affected by a geographical distance of trading partners.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 85%
“…Haggai (2016) used the traditional extended gravity model of international trade on a panel data covering 15 countries over a period of 15 years (2000–2014) to understand the Sino-Zambia trade relations. Doumbe and Belinga (2015) have used the gravity model to analyze the trade trend among Cameroon and 28 EU countries. Sejdini and Kraja (2014) have included the variables FTA and common border in their gravity model equation to analyze international trade in Albania.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Mauritius' Main Commodities Exported to China. Zambia trade relations Doumbe and Belinga (2015). have used the gravity model to analyze the trade trend among Cameroon and 28 EU countries Sejdini and Kraja (2014).…”
mentioning
confidence: 99%
“…The researchers used the gravity model to examine the trade flows between Cameroon and twenty-eight countries of the European Union. The findings revealed that Cameroon's foreign trade with the EU countries is positively influenced by economic size and per capita GDP and negatively affected by the distance between the trading partners (Doumbe & Belinga, 2015). The researchers the gravity model to analyze the influence of RTA on African agriculture exports.…”
Section: Literature Review About Using the Gravity Modelmentioning
confidence: 99%